Euglena gracilis and Its Aqueous Extract Constructed With Chitosan-Hyaluronic Acid Hydrogel Facilitate Cutaneous Wound Healing in Mice Without Inducing Excessive Inflammatory Response - Li, Jin; Zheng, Zezhou; Du, Ming; Chen, Jinchun; Zhu, Hui; Hu, Zhangli; Zhu, Yanxia; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2021)
Naturally occurring compounds isolated from the microalga Euglena gracilis, such as polysaccharide paramylon, exhibit antimicrobial, anti-viral, antitumor, and anti-inflammatory activities. Whether live E. gracilis cells and its aqueous extract accelerate burn wound healing remains to be investigated. In this study, live E. gracilis cells and its aqueous extract were mixed with chitosan-hyaluronic acid hydrogel (CS/HA) to form cell + CS/HA and extract + CS/HA, which were then smeared onto the deeply burned skin of mice. The efficacy of these mixtures in accelerating wound healing was assessed through wound size reduction measurement, histological and immunofluorescence analyses, and serum pro-inflammatory cytokine level (INF-γ, IL-1β, and IL-6) determination. The live E. gracilis cells and its aqueous extract were found to facilitate wound healing by enhancing re-epithelization and reducing fibroplasia without stimulating excessive inflammatory response. In conclusion, live E. gracilis cells and its aqueous extract can be potentially used to treat cutaneous wounds.